2017
DOI: 10.2174/1874210601711010404
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Appearances of Cervical Lymph Nodes in Healthy Turkish Adults Subpopulation: Preliminary Study

Abstract: Objectives:The aim of the study was to assess whether there was any relation between age, gender and body mass index (BMI) and nodal forms and vascular type in healthy Turkish adults.Study Design:Three neck areas in 25 wholesome patients who were aged from 21 to 58 years, were assessed by gray-scale and color doppler ultrasonography. Ultrasonographic examinations were performed using an ALOKA Prosound Alpha 6 (Hitachi Aloka Medical Systems, Tokyo, Japan) and the images were obtained with a 7.2 MHz linear array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…Another important predictor for cytologically confirmed malignancy is the nodal shape, as malignant nodes tend to be more round with a S/L ratio above 0.5 [10,27]. In our study we also found a significantly larger S/L ratio in cytologically malignant nodes than in benign nodes.…”
Section: Discussionsupporting
confidence: 70%
“…Another important predictor for cytologically confirmed malignancy is the nodal shape, as malignant nodes tend to be more round with a S/L ratio above 0.5 [10,27]. In our study we also found a significantly larger S/L ratio in cytologically malignant nodes than in benign nodes.…”
Section: Discussionsupporting
confidence: 70%
“…Okumuş et al . applied ultrasonography and found that the smallest-axis diameters of the submandibular and submental lymph nodes are 1.8 and 2.3 mm ( 14 ). In the present study, the smallest-axis diameters of the submandibular and submental lymph nodes were 2.2 and 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…For example in the study of Bennington et al ., [ 25 ], the thickness was measured at the anteroposterior midpoint of the muscle belly. In our study and the previous studies; measurements were performed at the point of estimated maximum thickness of muscle [ 19 , 20 ]. Bakke et al [ 30 ] also measured the thickness at the anteroposterior midpoint but they estimated the bulkiest level of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be greater in men and elderly individuals [ 21 , 36 ]. In a study conducted by Radsheer et al ., [ 19 ], it was reported that thickness of the masseter muscle decreases with age in both sexes. The similar results were portrayed in studies conducted by Kiliaridis & Kalebo [ 20 ] and Hernandez et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation